International Benchmarking of Infrastructure Performance in the Southern African Customs Union Countries - Bogetić, Željko; Fedderke, Johannes W. (World Bank, Washington, DC, 2012)
The paper provides a first, systematic benchmarking of infrastructure performance in the Southern African Customs Union (SACU) countries (South Africa, Botswana, Lesotho, Namibia, and Swaziland) in four major sectors-electricity, water and sanitation, information and communication technology, and transportation-against the relevant group of comparator countries using a new World Bank international data base with objective and perception-based indicators of infrastructure performance from over 200 countries. The analysis suggests important comparative gaps in all major infrastructure sectors, although performance varies widely across the SACU region. Performance shortfalls are particularly acute in rural areas where most of the poor live. The benchmarking is envisaged as a comparative input into deeper analyses of infrastructure performance, especially in the context of the ongoing scaling-up efforts (for example, South Africa, Lesotho, and Botswana).